Lát grǫn sía: Poetics of the Mouth in Egils saga and Vǫlsunga saga - Freya Alethe Schlaefer 2001- (2024)
This thesis examines the role and behavior of the mouth in Egils saga and Vǫlsunga saga. By using these two thirteenth-century sagas, the thesis aims to investigate the significances attached to the mouth in the residually oral, Christianized textual culture of medieval Iceland. Since sagas were generally preserved in manuscripts but also performed to audiences, there is significant tension in these texts around the role and prominence of the mouth. These concerns are exacerbated by increasing anxieties around food production which accompanied the onset of worse agricultural conditions during this period. The issue is also complicated by the intersection of paganism and Christianity inherent to post-conversion texts relying on pre-conversion art forms and narratives. This thesis examines how the presentation of the mouth in both sagas ultimately prizes oral adaptability and control above all else. Chapter one considers the mouth from a discursive perspective, examining characters’ mouths in terms of their dialogic and verbal capacity. It focuses primarily on the prosimetrum form and the flyting. Chapter two considers the mouth from the perspective of consumption, focusing on issues of food abundance and behavioral affirmation or alteration through foodstuff. Chapter three traces the development of the mouth through three male characters in each saga, exploring the ways in which each saga expresses changes to the mouth over generations. Hlutverk og hegðun munnsins í Egils sögu Skalla-Grímssonar og Vǫlsunga sögu er viðfangsefni þessarar ritgerðar. Markmiðið er að rannsaka merkingu þessa líffæris í kristinni textamenningu Íslands á miðöldum, þar sem enn ber mikið á munnlegri hefð. Fornsögurnar voru varðveittar í handritum en gjarnan fluttar áheyrendum. Því má greina spennu í textunum sem tengist hlutverki og sýnileika munnsins. Þessar áhyggjur verða því meiri sem kvíði vegna skertrar matvælaframleiðslu út af versnandi veðurskilyrðum eykst á þessum tíma. Það flækir málin að textarnir eru frá kristnum tíma en ...